The Influence of Principal’s Situational Leadership Style and Work Culture on the Professionality of Public Elementary School Teachers - Asnaini, Desi; Ahmad, Syarwani; Rohana, Rohana (Yayasan Sembilan Pemuda Indonesia, 2025)
This study examines the influence of principals’ situational leadership style and work culture on the professionalism of state elementary school teachers in Palembang. Specifically, it seeks to (1) assess the impact of situational leadership style on teacher professionalism, (2) analyze the effect of work culture on teacher professionalism, and (3) evaluate the combined influence of situational leadership and work culture on teacher professionalism. A quantitative approach was employed, with data collected from principals and teachers across several state elementary schools in Palembang. A pilot study was conducted at SD Negeri 143 Palembang, involving one principal and 31 teachers. The main study expanded to include teachers from SD Negeri 143, 144, 147, and 149 Palembang, using a 30-item questionnaire per variable. Data analysis was performed to determine the predictive power of the independent variables (leadership style and work culture) on teacher professionalism (dependent variable). The estimation trial yielded an R-squared value of 0.445, indicating that 44.5% of the variation in teacher professionalism is explained by situational leadership style and work culture, while the remaining 55.5% is attributed to other external factors. This study contributes to the existing literature by integrating situational leadership theory with work culture dynamics in the context of Indonesian elementary education, offering localized insights into factors shaping teacher professionalism. The findings suggest that school principals should adopt adaptive leadership strategies tailored to specific contexts while fostering a positive work culture to enhance teacher professionalism. Policymakers and school administrators can use these insights to design leadership training programs and cultural interventions that promote teacher development. This research provides empirical evidence on the interplay between leadership adaptability and organizational culture in improving teacher professionalism, offering a framework for educational institutions to strengthen workforce quality.